Results with a bench scale downdraft biomass gasifier for agricultural and forestry residues - ÖZDOĞAN, ZEYNEP SİBEL (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
A small scale fixed bed downdraft gasifier system to be fed with agricultural and forestry residues has been designed and constructed. The downdraft gasifier has four consecutive reaction zones from the top to the bottom, namely drying, pyrolysis, oxidation and reduction zones. Both the biomass fuel and the gases move in the same direction. A throat has been incorporated into the design to achieve gasification with lower tar production. The experimental system consists of the downdraft gasifier and the gas cleaning unit made up by a cyclone, a scrubber and a filter box. A pilot burner is utilized for initial ignition of the biomass fuel. The product gases are combusted in the flare built up as part of the gasification system. The gasification medium is air. The air to fuel ratio is adjusted to produce a gas with acceptably high heating value and low pollutants. Within this frame, different types of biomass, namely wood chips, barks, olive pomace and hazelnut shells are to be processed. The developed downdraft gasifier appears to handle the investigated biomass sources in a technically and environmentally feasible manner. This paper summarizes selected design related issues along with the results obtained with wood chips and hazelnut shells. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Downdraft gasifier; Fixed bed gasification; Throat; Wood chips; Hazelnut shell; ENERGY-PRODUCTION; GASIFICATION